Extension of Binary Topology - Seethalakshmi, R; Kamaraj, M (International Journal of Computer Sciences and Engineering, 2025)
Nithyanantha Jothi and Thangavelu studied the properties of the product of two power sets and introduced the concept of binary topology. In this paper, properties of the product of arbitrarily n-power sets are discussed where n >2. Further an n-ary topology on the product of power sets similar to binary topology is introduced and studied